Para usted, la tierra y, para usted, el mar: a propósito del extraño sentido de equidad de la cij en el asunto relativo a la Disputa territorial y marítima (Nicaragua c. Colombia) (2015)
The Territorial and Maritime Dispute (Nicaragua v. Colombia), one of the longest cases handled by the ICJ, seems far from being ended. Indeed, it has been ruled a decision on preliminary exceptions (2007), the judgment itself (2012) and two new applications (2013), always introduced by Nicaragua against Colombia. Leaving apart the procedural incidents or the requests of (previous or future) intervention of thirds, this article concentrates in the 2012 judgement, which in the author’s view, turns out as a strange expression of equity. Certainly, in its ruling, the Court decides to mutilate an archipelago –which has not ever defined– while leaving enclosed two maritime formations which were a part of the Archipelago of San Andrés, Providencia and Santa Catalina. Worse, the Court did not take into account the rights of the autochthonous population, neither environment nor regional security. Regarding the maritime delimitation, it constitutes the projection of the exclusive economic zone, but from the continental coast of Nicaragua, in detriment of the rights derived from the maritime formation of Colombia, which kept only what it already had possessed: the earth...